STUDI FENOMENOLOGI TATA KELOLA DANA DESA BERBASIS APLIKASI SISTEM KEUANGAN DESA - Arianto, Bambang; Gunawan, Agus (Program Studi Akuntansi Universitas Panca Bhakti, 2024)
This study aims to elaborate on the role of village financial applications in village fund governance. The Village Financial System (Siskeudes) application plays a role in improving governance and reporting of the use of village funds, so that it can strengthen indicators of transparency, accountability, and efficiency of village financial management. This study involved three subjects who were village government officials in the financial section and played a role in village fund governance. This study used a phenomenological study approach with the Interpretative Phenomenological Analysis analysis method. Data were obtained through in-depth interviews and observations with categories based on statements from research subjects on village government financial staff in Serang Regency. The research subjects stated that the Siskeudes application had made it easier to facilitate the village fund reporting process because it could reduce the administrative burden. This study found that the Siskeudes application could be used for audit purposes because it could maintain transaction history and was very compatible in its use. This greatly assists village government officials in the process of planning, implementing and reporting village finances. This study also found that through the use of the Siskeudes application, the audit and evaluation process of the use of village funds can be carried out properly, so that it can strengthen the aspects of accountability and transparency as the main indicators of village financial governance. Keywords: Village Funds; Village Financial System Application; Fraud Prevention